2018
DOI: 10.1093/ibd/izy237
|View full text |Cite
|
Sign up to set email alerts
|

Limited Health Literacy Is Associated With Worse Patient-Reported Outcomes in Inflammatory Bowel Disease

Abstract: Limited health literacy is associated with lower ratings of subjective health and depression in IBD and more symptoms of active disease in patients with Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 61 publications
2
48
0
Order By: Relevance
“…For example, it may affect the ability of patients to follow written instructions for medications (28) or engage in self-care, and it has been linked to nonadherence to medications (9). The association of limited health literacy with worse scores on patient-reported outcomes noted in the study of patients with IBD also found that patients with limited health literacy had more symptoms of active disease (26). In RA, limited health literacy has been associated with health outcomes, poorer functional status, and more health care use (9,10,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it may affect the ability of patients to follow written instructions for medications (28) or engage in self-care, and it has been linked to nonadherence to medications (9). The association of limited health literacy with worse scores on patient-reported outcomes noted in the study of patients with IBD also found that patients with limited health literacy had more symptoms of active disease (26). In RA, limited health literacy has been associated with health outcomes, poorer functional status, and more health care use (9,10,29).…”
Section: Discussionmentioning
confidence: 99%
“…For example, low health literacy was associated with large, clinically significant decrements in Health Assessment Questionnaire scores among a large cohort of individuals with RA, even after accounting for educational attainment (9). Likewise, limited health literacy was associated with lower ratings of health status and quality of life among individuals with inflammatory bowel disease (IBD) (26). Other investigators have proposed that health literacy may at least partially mediate educational and racial/ethnic disparities in some health outcomes (27), but we found only limited evidence of such mediation in our analyses because low education was much less frequently associated with the patient‐reported outcomes, even without considering health literacy; i.e., there was little effect of low education to be mediated.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with lower health literacy are more likely to be noncompliant with treatment and to report higher unmet informational needs and more mental distress, which may contribute to overall poorer QOL. 35,36,44,45 Early intervention to improve patient understanding and health literacy, therefore, may improve patient QOL not only during but after treatment. Prior research has shown that interventions to improve health literacy resulted in a higher rate of patient adherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted that Crohn's disease patients with limited health literacy have more symptoms of active disease, more depression, and worse overall health status. 1 Low health literacy has been associated with difficulty managing chronic conditions, decreased medication adherence, and more hospitalizations. 2,3 Additionally, there are simple health literacy screening tools that can be easily administered.…”
Section: To the Editorsmentioning
confidence: 99%